2020
DOI: 10.1101/2020.06.05.20123042
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Era of Coronavirus; Knowledge, Attitude, Practices, and Barriers to Hand Hygiene Among Makerere University Students and Katanga Community Residents

Abstract: Background China reported the Novel Coronavirus at the end of the year 2019 which was, later on, declared a Pandemic by the WHO. Proper hand hygiene was identified as one of the simplest most cost effective Covid-19 control and prevention measures. It is therefore very important to understand the compliance of the community to hand hygiene. Method A descriptive cross-sectional study was conducted among the undergraduate students of Makerere University and residents of Katanga slum from 17th to 22nd of March, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Yet 71 (59.2%) mentioned that hand hygiene supplies are inaccessible, hence difficult to practice hand hygiene. These findings were in line with other studies that indicated that the commonest barriers to hand hygiene were lack of soaps, antiseptics, detergents, alcohol sanitizers, lack of running water, and negligence [18]. Other findings that were no different from this assertion were studies that opined that hand hygiene supplies were inadequate and hence acted as barriers to standard hand hygiene practice [8,18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Yet 71 (59.2%) mentioned that hand hygiene supplies are inaccessible, hence difficult to practice hand hygiene. These findings were in line with other studies that indicated that the commonest barriers to hand hygiene were lack of soaps, antiseptics, detergents, alcohol sanitizers, lack of running water, and negligence [18]. Other findings that were no different from this assertion were studies that opined that hand hygiene supplies were inadequate and hence acted as barriers to standard hand hygiene practice [8,18].…”
Section: Discussionsupporting
confidence: 88%
“…Student nurses are often seen to be novice and not capable of effectively complying with standard preventive strategies [17]. A study conducted in Uganda among students of Makerere University and Katanga community residents came out that 8.4% of the participants had good knowledge of hand hygiene [18]. It is, therefore, imperative to assess nursing students' perceptions of barriers to hand hygiene practice amidst COVID-19 because nursing students are the future workforce and their perceptions about hand hygiene barriers would provide an opportunity to address any barriers to hand hygiene practices.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of respondents reporting barriers to handwashing was substantially lower than in a study among students and slum dwellers in Uganda, where 60.1% reported lack of soap, detergents, alcohol-based hand rub, or antiseptic as a barrier to handwashing, and 33.9% reported lack of running water as a barrier. 18 These findings illustrate how the provision of soap and a reliable water supply are needed to enable individuals to practice the promoted preventative measure of handwashing. This is also in line with common behavior change theories, which include the concept of having an enabling physical environment as a requisite for behavioral performance.…”
Section: Discussionmentioning
confidence: 95%
“…The proportion of respondents reporting barriers to handwashing was substantially lower than a study among students and slum dwellers in Uganda where 60.1% reported lack of soap, detergents, alcohol-based hand rub, or antiseptic as a barrier to handwashing and 33.9% reported lack of running water as a barrier. 18 These findings illustrate how the provision of soap and reliable water supply are needed to enable individuals to practice the promoted preventative measure of handwashing. This is also in line with common behavior change theories which include the concept of having an enabling physical environment as a requisite for behavioral performance.…”
Section: Discussionmentioning
confidence: 95%